CALCULATION OF THE REQUIRED PERFORATION INTENSITY FOR THE LATERAL SURFACE OF DISTRIBUTION DRAINAGE PIPELINES - Kravchuk, O. (Municipal economy of cities. Series: «Economy science», 2025)
This paper considers the operation features of a pressure distribution drainage pipeline, where the fluid leakage along the length occurs through holes and slots in the side walls in filtration mode. In this case, the filtration mode of fluid leakage from the pipeline is ensured by using various types of rolled filter material for wrapping the drain. At the same time, the fluid within the pipeline moves in a turbulent mode. Based on a comparison of the calculated dependencies used to describe the law of fluid leakage from pipelines in each case, namely, leakage from perforation holes and through the filter material, relatively simple and convenient calculation formulas are derived for determining the required degree of the side walls perforation of the drainage pipeline, ensuring the leakage of a given water flow from the distributor. The degree of perforation S is understood as the ratio of the area of the perforation holes (slots) in the side walls of the drainage pipeline to the total area of its side surface. The parameter A, which comprehensively takes into account the design and filtration characteristics of drainage pipelines, is used in the analysis of the operation of the considered pipes. Additionally, when determining the flow rate in the initial cross-section of the distribution pipeline, the concept of an infinitely long drainage pipeline, or equivalently, a pipeline with infinitely large penetration along its side wall surface, is introduced. Corresponding analytical dependencies and a graph are presented for determining the searched parameters. It is shown that the degree of perforation is influenced by both the structural characteristics of the pipeline itself and the filtration properties of the surrounding soil and the surface of the drainage pipes. Moreover, the proposed methodology for calculating the perforation intensity ensures an even placement of holes along the length of the distribution pipe.